Satisfação da família e requisitos para o desenvolvimento de dispositivos de tecnologia assistiva para a mobilidade infantil - Linhares, Bianca de Medeiros Rodrigues (2024)
Introduction: Mobility can be considered an important activity for engagement in several significant childhood occupations, as well as in different contexts, and is among the domains presented by the World Health Organization (WHO) in the International Classification of Functioning, Disability and Health (CIF), as part of the Activity and Participation component. Functional mobility is presented, by the American Occupational Therapy Association (AOTA), as part of the occupation of Activities of Daily Living (ADLs), being defined as the ability of an individual to move or change from one position to another. another, when carrying out daily activities, whether this movement is in a sitting or standing position. Assistive Technology (AT), which is among the environmental factors of the ICF, can play a facilitating role in the mobility of children with disabilities. Objectives: Identify the level of independence in mobility of children with disabilities and investigate family satisfaction regarding the assistive technology devices used, to understand family members' opinions and carry out a survey of the necessary requirements for new equipment, to subsidize the process of innovation and mobility device development. Methods: This is a cross-sectional, descriptive research, aiming to carry out a field study with families of children aged 0 to 11 years old, who have mobility restrictions, as well as an exploratory stage, to obtain data for innovation and technological development in this area. Data collection took place in three stages: in the first, an electronic form was applied on AT devices; in the second, an individual interview to apply two standardized instruments, the Pediatric Disability Assessment Inventory - Adaptive Computerized Testing (PEDI-CAT) and the Brazilian version of the Quebec Assessment of User Satisfaction with Assistive Technology (B-QUEST 2.0) ; and, finally, in the third stage, focus groups were held with family members, to provide an opportunity for a debate on mobility devices and carry out a collection with a qualitative approach, in a complementary way to the quantitative approach of the other stages. Results: Ten families participated in the study, all of whom declared that the children's mobility restrictions were due to the diagnosis of cerebral palsy, with functional delays in terms of mobility, as they scored below 30 on the normative score, measured by the PEDI CAT. All children use AT devices for mobility, which are: manual wheelchair with adaptations (50%), manual wheelchair without adaptations (30%), baby stroller (10%) and walker without body support (10%). Most of the equipment was acquired through donations from third parties (50%) and it was verified, through the application of QUEST, that the participating family members had a high level of satisfaction with them, with the average of the eight items in the first part of the instrument, considering the scores of all participants, was between 4.3 and 4.9, that is,between “quite satisfied” and “completely satisfied”. The aspects chosen as the most important in assistive devices by families refer to: “Ease of adjustment”, “Ease of use”, “Comfort” and “Stability and safety”. In the third stage of the research, many experiences were shared, and concrete solutions were thought of by family members. Final Considerations: The study made important contributions to the AT area, valuing the involvement and perspective of family members, whose satisfaction was measured and whose opinions were collected through focus groups, a method that proved to be powerful in promoting debate in this area. Six categories were obtained, based on family members' reports: Positive aspects of the device, Benefits, Negative aspects, Challenging situations, Requirements for the development of wheelchairs and new mobility equipment. It is considered that the child's satisfaction and the evaluation of a specialized team could bring different data and relevant information, in a complementary way, which points to the importance of future work. It is concluded that the objectives were achieved and that the results made it possible to bring the interdisciplinary research team closer to the particularities involving the use of mobility aid devices by children with disabilities and their families, and the understanding of important aspects to direct the development of new concepts and prototypes in AT for child mobility.